REPRODUCTIVE CLONING AND A (KIND OF) GENETIC FALLACY - Levy, Neil (Bioethics, 2005)
Many people now believe that human reproductive cloning – once sufficiently safe and effective – should be permitted on the grounds that it will allow the otherwise infertile to have children that are biologically closely related to them. However, though it is widely believed that the possession of a close genetic link to our children is morally significant and valuable, we argue that such a view is erroneous. Moreover, the claim that the genetic link is valuable is pernicious; it tends to give rise to highly undesirable consequences, and therefore should be combated rather than pandered to. The emphasis on the genetic is unwarranted and unfortunate; rather than giving us moral reason to support reproductive cloning in the case of infertility, the fact that cloning requests are likely to be motivated by the genetic argument gives us reason to oppose its availability.